Wavelength dispersive X-ray fluorescence (WDXRF) and chemometric investigation of human hair after cosmetic treatment - Santos, Mônica Cardoso [UNESP]; Sperança, Marco Aurelio; Pereira, Fabíola Manhas Verbi [UNESP] (Wiley, 2018)
Variations in the chemical composition of 63 different human and 6 different synthetic hair samples were investigated using wavelength dispersive X-ray fluorescence (WDXRF) spectra profiles. To evaluate the effect of cosmetic treatment on the strands, the human hair samples were bleached, but the synthetic ones were not. To better investigate the data, exploratory analyses were calculated using principal component analysis for the WDXRF spectra. Eight normalizations/standardizations were applied in the WDXRF to verify the clustering tendency. Bleaching was tested, because it is one way in which people mask their real hair color. After the data were standardized, an enhancement of the data discrimination was verified. Furthermore, the explained variance was higher in the first principal components. The WDXRF spectra were able to distinguish samples with distinct features, including synthetic, dyed, and straightened hair. The findings of this study hold promise for forensics due to desirable aspects such as nondestructivity and the possibility of a large hair sample database.